ANALYSIS OF FIGURATIVE LANGUAGE IN THE LYRICS OF THE SONG ENTITLED 'I SEE THE LIGHT' IN THE DISNEY MOVIE TANGLED - Ni Putu Anggie Kusuma Wardhani (LPPM Universitas Dhyana Pura, 2023)
This research aims to analyze the use of figurative language in the song entitled